A randomised controlled study of effectiveness of patient information leaflets on systemic lupus erythematosus (SLE) in improving knowledge on SLE - Galappatthy, P.; Dharmarathne, N.; Fernando, V.; Dayasiri, K.; Perera, M.T.K.; Sheriff, M.H.R. (My University, 2009)
Providing information about the disease and treatment is important particularly for patients with a complex chronic disease. Objectives: To evaluate the effectiveness of patient information leaflets in improving the knowledge on SLE compared to a control group who did not receive leaflets. Methodology: Six patient information leaflets were developed on SLE and its treatment. A patient knowledge questionnaire was developed and validated. Intervention and control groups were recruited from patients with SLE, diagnosed on ACR criteria, attending the University Lupus Clinic. The mean knowledge score(MKS) at baseline and 4-6 weeks after giving leaflets to intervention group allocated by block randomisation was compared using unpaired t test in SPSS and Graphpad Instat statistical packages. Steps were taken to shield the control group from leaflets. Results: Out of 100 participants (48 in Intervention), 89 (41 in intervention) completed the 2nd session. The MKS in the total population at base line was 38.9 out of 63 (61.7 %). The total MKS was not significantly different (P=0.314) between the control (39.3) and intervention (41.0) groups at baseline. The total MKS significantly improved (P=0.0001) in intervention (53.6; 85.1%) than in control group (45.9; 78.6%) following intervention. The baseline knowledge was poor on contraception, pregnancy and side effects of drugs. Significant improvement in knowledge occurred on these aspects and on signs and symptoms, common myths and drug storage. Statistically significant improvement occurred in compliance as reported by patients, in the intervention group (SND=3.35, P<0.001). Conclusion: Patient information leaflets lead to significant improvement in overall knowledge and on important aspects of SLE.